When Oracles Go Wrong: Using Preferences as a Means to Explore. - Sheidlower, Isaac S.; Short, Elaine Schaertl. (Tufts University. Tisch Library., 2023)
Keywords: human-robot interaction, interactive reinforcement learning.; Topic: Computing methodologies / Artificial intelligence; ACM Open.